The Relationship Between Cadre Mentoring and Adolescent Participation in Youth Posyandu Activities - Hasanah, Ainani; Rita Yulifah; Ari Kusmiwiyati (Health Access Journal, 2025)
Adolescence is a critical developmental period that strongly influences reproductive health, where insufficient knowledge may increase the risk of unwanted pregnancy and sexually transmitted infections. The youth posyandu plays an important role in providing reproductive health education; however, adolescent participation remains low due to limited awareness, stigma, and restricted access to information. This study aimed to examine the relationship between cadre mentoring and adolescent participation in youth posyandu activities in Petungsewu Village, Dau Subdistrict, Malang Regency. A correlational analytic design with a cross-sectional approach was employed, involving 18 cadres and 35 adolescents actively engaged in youth posyandu activities, selected through total sampling. Data were collected using a structured questionnaire and analyzed with the Spearman rank test. Results showed that 50% of cadres provided good mentoring, while 74.3% of adolescents demonstrated moderate participation. The Spearman rank test yielded a p-value of 0.028 and a correlation coefficient of 0.518, indicating a significant positive relationship between cadre mentoring and adolescent participation. It can be concluded that continuous and structured cadre mentoring effectively enhances adolescent engagement in youth posyandu activities. Appropriate mentoring approaches may strengthen adolescents’ sense of support, motivation, and knowledge, thereby encouraging more active participation.Keyword: Adolescent Health; Adolescent Participation, Cadre Assistance, Youth Posyandu